2020
DOI: 10.1177/1056789520974416
|View full text |Cite
|
Sign up to set email alerts
|

Expansive soil-biochar-root-water-bacteria interaction: Investigation on crack development, water management and plant growth in green infrastructure

Abstract: The objectives of the study are to explore fundamental mechanism of expansive soil-biochar-root-water-bacteria interaction, and investigate crack development and hydraulic properties of biochar amended soils aiming at green infrastructures. The physical, chemical and biological effects of biochar on expansive soil have been comprehensively explored. Crack development is investigated quantificationally, and mechanism of soil damage evolution is briefly discussed base on micro-chemical analyses. During outdoor v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Other studies have demonstrated that other characteristics of the growing medium, like its organic content, nutrients or pH, are important (Nagase and Dunnett, 2011;Bates et al, 2013;Kotsiris et al, 2013;Thuring and Dunnett, 2014;Tassoula et al, 2015;Papafotiou et al, 2016;McAlister and Rott, 2019). Further studies have investigated the influence of different types of substrates (A'saf et al, 2020;Paraskevopoulou et al, 2021), or other parameters relating with the substrate like the role of bacteria in the soil (Xie et al, 2020;Wang et al, 2021), on plant performance, or on the functions of green roofs (Naranjo et al, 2020). Bates et al (2013) investigated vegetation development on low-fertility growth substrates emulating brownfields and their responses to drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated that other characteristics of the growing medium, like its organic content, nutrients or pH, are important (Nagase and Dunnett, 2011;Bates et al, 2013;Kotsiris et al, 2013;Thuring and Dunnett, 2014;Tassoula et al, 2015;Papafotiou et al, 2016;McAlister and Rott, 2019). Further studies have investigated the influence of different types of substrates (A'saf et al, 2020;Paraskevopoulou et al, 2021), or other parameters relating with the substrate like the role of bacteria in the soil (Xie et al, 2020;Wang et al, 2021), on plant performance, or on the functions of green roofs (Naranjo et al, 2020). Bates et al (2013) investigated vegetation development on low-fertility growth substrates emulating brownfields and their responses to drought conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, erosion studies about soil-biochar composite mainly discuss the influence of biochar characteristics, such as biochar percentage [49,53] and biochar particle size [56]. There are studies that exist on studying the influence of the type of biochar on the performance of green infrastructure, including water retention [57,58], nutrient leaching mitigation [59], and pollutant removal from runoff [60]. However, few studies have documented the effects of different types of biochar on erosion, runoff, and infiltration [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…First, the idea and fundamental value of GI have been the major emphasis of much research. By looking for publications on GI in four different databases, including books, documents from global agencies, Web of Science (WOS), research institutes, and federal agencies up to 2016, Wang, Zhang, Gan, Liu, and Mei [17] provided a summary of green infrastructure's growth up to that point; they also stressed the significance if multi-function for the analysis and design of GI. Second, a subfield of green infrastructure has been the subject of a comprehensive scholarly analysis.…”
Section: Background Analysismentioning
confidence: 99%